2020
DOI: 10.1002/cbf.3528
|View full text |Cite
|
Sign up to set email alerts
|

Robust expression of SIRT6 inhibits pulpitis via activation of the TRPV1 channel

Abstract: Invasion of dentinal tubules and pulp tissue by pathogenic bacteria may cause infection leading to pulpitis. Sirtuin 6 (SIRT6) is a NAD‐dependent protein deacetylase encoded by the SIRT6 gene. The effect of SIRT6 on lipopolysaccharide (LPS)‐induced pulpitis and its mechanism of action were discussed in this study. Dental pulp cells (DPCs) were extracted from human teeth and injected with LPS to induce inflammation. The cells injected with LPS showed substantially decreased expression of SIRT6. The overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Another way LPS works is by activating transient receptor potential vanilloid 1 (TRPV1) canal. Overexpression of SIRT6 protein, which promotes degradation of TRPV1 via its ubiquitination, reduces expression of cytokines—IL-6, IL-1β, and TNF-α, deactivates NF-κB and lowers DMP1 level [ 107 ]. Capsaicin stimulates TRPV1 in SIRT6-overexpressed cells, counteracting anti-inflammatory properties [ 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another way LPS works is by activating transient receptor potential vanilloid 1 (TRPV1) canal. Overexpression of SIRT6 protein, which promotes degradation of TRPV1 via its ubiquitination, reduces expression of cytokines—IL-6, IL-1β, and TNF-α, deactivates NF-κB and lowers DMP1 level [ 107 ]. Capsaicin stimulates TRPV1 in SIRT6-overexpressed cells, counteracting anti-inflammatory properties [ 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is worth noting that SIRT6 has been suggested to take a part in TRPV1-mediated inflammation. In the inflammatory state, the level of SIRT6 was decreased while TRPV1 expression was upregulated [ 30 , 77 ]. Overexpression of SIRT6 could suppress TRPV1 and result in significant downregulation ROS and NF- κ B production, achieving anti-inflammatory effect [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT6 has been well established to promote nuclear factor erythroid 2-related factor 2 (Nrf2) binding the antioxidant response elements (AREs) and to protect cells from oxidative stress [ 29 ]. Additionally, robust expression of SIRT6 has been shown an inhibitory effect on TRPV1-regulated inflammation [ 30 , 31 ]. Thus, promoting the SIRT6/Nrf2 signaling will be a distinctive strategy to curb IR.…”
Section: Introductionmentioning
confidence: 99%
“…[139][140][141] In lipopolysaccharideinduced pulpitis, Hu et al demonstrated that overexpression of SIRT6 led to a significant reduction in proinflammatory cytokines (IL-6, IL-1 β, and TNFα) and inactivation of the NF-κB pathway, thereby attenuating pain caused by pulpitis. 142 Therefore, the above evidence indicates that other sirtuins may act as potential targets for the prevention and treatment of chronic pain. Large-scale, multicenter, prospective clinical trials are needed.…”
Section: Con Clud Ing Remark S and Future Per S Pec Tivementioning
confidence: 99%
“…It has been reported that SIRT3 improves the ability of mitochondria to reduce ROS levels and protect against oxidative stress by regulating the activity of key antioxidant enzymes, such as manganese superoxide dismutase 139‐141 . In lipopolysaccharide‐induced pulpitis, Hu et al demonstrated that overexpression of SIRT6 led to a significant reduction in proinflammatory cytokines (IL‐6, IL‐1 β, and TNF‐α) and inactivation of the NF‐κB pathway, thereby attenuating pain caused by pulpitis 142 . Therefore, the above evidence indicates that other sirtuins may act as potential targets for the prevention and treatment of chronic pain.…”
Section: Concluding Remarks and Future Perspectivementioning
confidence: 99%